The usage of soft modelling to research the relationship between human capital and the economic development level in Polish regions - Skrodzka, Iwona (Zastosowanie modelowania miekkiego do pomiaru zależności między kapitałem ludzkim a poziomem rozwoju gospodarczego w polskich województwach, 2012)
The aim of this article is to present research results of the relationship between human capital and economic development level in Polish regions. The method which was used in this study was soft modelling. Soft modelling enables to investigate the relationship among unobserved variables (latent variables). Human capital and economic development can be classified into these types of categories. The presented soft model contained four latent variables: human capital, investments in human capital, physical capital and the level of economic development. The results of the research allowed us to verify which of two forms of capital: human or physical, had the stronger influence on the level of economic development in Polish regions. Moreover they enabled to put regions into order in terms of the human capital stock, human capital investments and the economic development level
Ekonometria = Econometrics, 2012, Nr 1 (35), s. 24-37
Keywords: human capital; economic development; soft modelling; kapitał ludzki; rozwój gospodarczy; modelowanie miękkie